ANALISA PENGARUH KRISIS GLOBAL FINANCIAL TERHADAP JAKARTA ISLAMIC INDEX (JII) DAN INDEX HARGA SAHAM GABUNGAN (IHSG) - Fitriany Fitriany (Jurnal Ekonomi & Keuangan Islam, 2012)
The financial crisis in the United State on September 2008 has created global impact to the world economy, including the performace of capital markets. Most of market indexes around the world fall down significantly, including marketÂ  indexes in Bursa Efek Indonesia (BEI). There were five market index in BEI, namely IHSG, LQ 45, MBX, DBX,  and JII. This research is mainly aim to examine the influence of the US financial crisis to the performace of JII and IHSG. In addition, the  relation ofÂ  JII and IHSG to DowJones Index, Tokyo Index, and Hongkong Index  are also examined. To get the aim done, a Vector Autoregressive Model (VAR) is utilized. VAR is an appropriate model to examine a simultaneous relationship with capability to tract impulse response among variables. The research findings show the US financial crisis has created significant shocks toward JII and IHSG during September to October 2008. Both IHSG and JII has constantly decrease during 8 weeks, but IHS was getting recovered quicker than JII. The investment rather than speculation motive of the players in JII cound be the answer for this finding.